Proline functionalization of the mesoporous metal-organic framework DUT-32 - Kutzscher, Christel; Hoffmann, Herbert C.; Krause, Simon; Stoeck, Ulrich; Senkovska, Irena; Brunner, Eike; Kaskel, Stefan (Inorganic Chemistry, 2015)
The linker functionalization strategy was applied to incorporate proline moieties into a metal-organic framework (MOF). When 4,4′-biphenyldicarboxylic acid was replaced with a Boc-protected proline-functionalized linker (H2L) in the synthesis of DUT-32 (DUT = Dresden University of Technology), a highly porous enantiomerically pure MOF (DUT-32-NHProBoc) was obtained, as could be confirmed by enantioselective high-performance liquid chromatography (HPLC) measurements and solid-state NMR experiments. Isotope labeling of the chiral side group proline enabled highly sensitive one- and two-dimensional solid-state 13C NMR experiments. For samples loaded with (S)-1-phenyl-2,2,2-trifluoroethanol [(S)-TFPE], the proline groups are shown to exhibit a lower mobility than that for (R)-TFPE-loaded samples. This indicates a preferred interaction of the shift agent (S)-TFPE with the chiral moieties. The high porosity of the compound is reflected by an exceptionally high ethyl cinnamate adsorption capacity. However, postsynthetic thermal deprotection of Boc-proline in the MOF leads to racemization of the chiral center, which was verified by stereoselective HPLC experiments and asymmetric catalysis of aldol addition.
CRIS-Team Scopus Importer:2023-03-20